NCFU - ENTERING THE 6TH TECHNOLOGICAL CYCLE (SCIENTOMETRIC ANALYSIS) - Anna V. Savtsova; Victor M. Averbukh (Вестник Северо-Кавказского федерального университета, 2022)
Of the thirteen problematic positions within the 6th TC, the research at the NCFU is held in 5 areas, which is done at thirteen departments and one research center. 19 subjects (14.25%) correspond to the following five areas of the 6th TC: Robotics - 1; Biotechnology - 3; Nanotechnology - 9; Global Information Network - 4; Space technology - 2 theme for research projects.